Petrophysical evaluation of the hydrocarbon potential of the Lower Cretaceous Kharita clastics, North Qarun oil field, Western Desert, Egypt. (September 2016) - Teama, Mostafa A.; Nabawy, Bassem S.
Abstract: Based on the available well log data of six wells chosen in the North Qarun oil field in the Western Desert of Egypt, the petrophysical evaluation for the Lower Cretaceous Kharita Formation was accomplished. The lithology of Kharita Formation was analyzed using the neutron porosity-density and the neutron porosity-gamma ray crossplots as well as the litho-saturation plot. The petrophysical parameters, include shale volume, effective porosity, water saturation and hydrocarbon pore volume, were determined and traced laterally in the studied field through the iso-parametric maps. The lithology crossplots of the studied wells show that the sandstone is the main lithology of the Kharita Formation intercalated with some calcareous shale. The cutoff values of shale volume, porosity and water saturation for the productive hydrocarbon pay zones are defined to be 40%, 10% and 50%, respectively, which were determined, based on the applied crossplots approach and their limits. The iso-parametric contour maps for the average reservoir parameters; such as net-pay thickness, average porosity, shale volume, water saturation and the hydrocarbon pore volume were illustrated. From the present study, it is found that the Kharita Formation in the North Qarun oil field has promising reservoir characteristics, particularly in the northwestern part of the study area, which is considered as a prospective area for oil accumulation. Highlights: Lithology crossplots show that sandstone is the main lithology of Kharita Formation. Kharita Formation in north Qarun oil field has promising reservoir characteristics. Oil potential increases to the NW of the studied area.